2010
DOI: 10.1098/rsta.2009.0250
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for magnetic field reversals

Abstract: We present a review of the different models that have been proposed to explain reversals of the magnetic field generated by a turbulent flow of an electrically conducting fluid (fluid dynamos). We then describe a simple mechanism that explains several features observed in palaeomagnetic records of the Earth's magnetic field, in numerical simulations and in a recent dynamo experiment. A similar model can also be used to understand reversals of large-scale flows that often develop on a turbulent background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Field reversals and associated symmetry changes arise also in several related systems, notably the geodynamo (e.g. Roberts and Glatzmaier 2000;Pétrélis et al 2009;Pétrélis & Fauve 2010;Gallet et al 2012) and the VKS experiment, where dynamo action is driven by ferromagnetic rotors in a tank of molten sodium (Ravelet et al 2008;Monchaux et al 2009;Berhanu et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Field reversals and associated symmetry changes arise also in several related systems, notably the geodynamo (e.g. Roberts and Glatzmaier 2000;Pétrélis et al 2009;Pétrélis & Fauve 2010;Gallet et al 2012) and the VKS experiment, where dynamo action is driven by ferromagnetic rotors in a tank of molten sodium (Ravelet et al 2008;Monchaux et al 2009;Berhanu et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, they can also trigger dynamical reversals between different metastable states, although it has also been reported that, within the experimental observation times, on occasion these fluctuations do not induce such reversals [17]. The search for generic mechanisms for reversals has been initiated and some simple low dimensional models, where for example an unstable mode is coupled to other stable modes, have been proposed [19,20]. It would be interesting to go beyond the quintic subcritical amplitude equation that we propose in this work, searching for such a simple model of interacting modes.…”
Section: Resultsmentioning
confidence: 99%
“…Turbulent flows that present bistability and hysteresis have been studied in the contexts of pure fluid dynamics [10][11][12][13][14][15] and magnetohydrodynamics, particularly concerning the Dynamo instability [16][17][18]. An interesting issue is the possibility of random reversals between two turbulent attractors [10,13,16,19,20]. More generally, the existence of large-scale fields on top of strongly turbulent backgrounds is also present in many geophysical and astrophysical flows.…”
Section: Introductionmentioning
confidence: 99%
“…Such effects had been neither observed in the Riga nor in the Karlsruhe experiment and thus instigated a strong interest in the geophysics community, with a number of attempts to understand reversals of the geomagnetic field and reversals in the VKS dynamo on the common basis of low-dimensional models [45].…”
Section: Forward Problems: One Examplementioning
confidence: 99%